Studi Relationship Marketing Dalam Mempengaruhi Kualitas Kinerja PLUT-KUMKM Sebagai Pelayan Publik - Emi Habiburohmah; Farida Indriani (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Micro, Small and Medium Enterprises (MSMEs) are the largest majority of the total business population in Indonesia, which unfortunately are still experiencing various chronic problems that make MSMEs to develop and advance to class. To assist MSMEs in developing their businesses, the Ministry of Cooperatives and SMEs since 2013 has built the KUMKM Integrated Business Service Center which until 2020 has been in 71 regions throughout Indonesia. As a public servant, especially MSMEs, PLUT-KUMKM has experienced a decline in the participation of MSME assistance until 2020. The performance of PLUT-KUMKM as a public servant cannot be separated from how to maintain relationships with stakeholders in the marketing environment. This study aims to find out how PLUT-KUMKM maintains relationships with its stakeholders, how PLUT-KUMKM meets the expectations of stakeholders and how this affects the performance of public services carried out by PLUT-KUMKM. This research is a descriptive research with qualitative methods. The data was collected by interview and secondary data with the respondents being the 4 stakeholders PLUT-KUMKMThe results of this study are that there are differences in the fulfillment of expectations in maintaining the relationship between PLUT-KUMKM and stakeholderswhich results in differences in the achievement of targets and targets from one PLUT-KUMKM with other PLUT-KUMKM. The responses from each stakeholder can be used as input for efforts to improve the Management of PLUT-KUMKM from the Central and Regional levels for better distribution of Public Service Performance of PLUT-KUMKM.